Loneliness: a lifelong learning (Journal of Parents and Teachers, 1996)
Loneliness is a complex issue that affects people of all ages, often stemming from poor family relationships and social problems. It can be both a refuge and an obstacle in the creative and emotional process. Overcoming loneliness involves learning to live with it and transforming it into a positive experience.
Keywords: loneliness; creativity; relationships; positive experience